HASAN AL-BASRI AS THE FOUNDER OF THE ZAHID MOVEMENT - Alimov Kh.M. (Western European Studies, 2024)
This article is devoted to the issue of asceticism, which is one of the important stages in the history of Sufism. It is known that Hasan Basriy is one of the founders of the ascetic stage. He is the founder of a scientific school called the Basra school in the history of Sufism. He creates the religious foundations of the ascetic movement.
Keywords: life and work of Hassan al-Basri; cognitive theory; ascetic movement; Sufism